The current status and efficiency of the use of land resources in Odessa region - Kostiukievych, T.; Danilova, N.; Tolmachova, А.; Movchan, Т.; Malashchuk, О. (Land Management, Cadastre and Land Monitoring, 2025)
Effective and rational use of land resources is of paramount importance for the agricultural economy both at the level of individual enterprises and on a national scale. The paper examines the state and efficiency of land resources use in Odessa region in terms of natural agricultural zones. It was determined that in the structure of agricultural lands of the region, the largest part is arable land - 80.25%. An analysis of the dynamics of land resources of the region and the dynamics of the efficiency of their use by natural indicators we conducted. The results obtained indicate the dynamics of growth of areas under winter wheat, rapeseed and sunflower, and the stability of corn and barley crops was established. It is worth noting that in most cases the increase in gross harvest occurred due to an increase in sown areas. For a more detailed analysis, the level of sunflower yield we investigated in terms of administrative districts in relation to natural agricultural zones. The results obtained indicate that the lowest level of yield is observed in the Steppe arid zone, which is explained by arid conditions. Based on the analysis, a set of measures for optimizing land use is proposed, aimed at increasing the efficiency of land resource use in the region.Keywords: land resources, cadastre, efficiency of use, natural agricultural zone, yield, geospatial data infrastructure, land reclamation, land management, productivity, agricultural lands, optimization of use.
Keywords: land resources; cadastre; efficiency of use; natural agricultural zone; yield; geospatial data infrastructure; land reclamation; land management; productivity; agricultural lands; optimization of use